Complexation and transport of transition and heavy metal cations by p-tert-butyldihomooxacalix[4]arene tetraketones and X-ray crystal structure of the tert-butyl ketone derivative - Marcos, Paula M. (2015)
The binding properties of three p-tert-butyldihomooxacalix[4]arene tetraketone derivatives ( tertbutyl 2b, adamantyl 2c and phenyl 2d) in the cone conformation and one derivative ( methyl 2a) in a partial cone conformation, towards transition ( Mn2+, Fe2+, Co2+, Ni2+, Cu2+ and Zn2+) and heavy (Ag+, Cd2+, Hg2+ and Pb2+) metal cations have been established by extraction studies of metal picrates from water into dichloromethane, transport experiments with the same salts through a dichloromethane membrane and stability constant measurements in methanol and acetonitrile. Results concerning the microcalorimetric study of Cu2+, Ag+ and Pb2+ complexes in methanol are presented. The affinity of the ligands for some cations ( Zn2+, Ag+, Pb2+ and Hg2+) has also been investigated by proton NMR spectrometry. The X-ray crystal structure of tert-butylketone 2b was determined. Towards transition metal cations, ketones 2b, 2c and 2d are reasonable binders, showing in general preference for Cu2+. Methylketone 2a is a poor binder for these cations, due to its partial cone conformation. The three ligands in the cone conformation present a high affinity for the heavy metal cations, with selectivities for Ag+ and Pb2+. This series of cations is even fairly well complexed by methylketone 2a, which presents high stability constants for Hg2+ and Pb2+. The cases studied by H-1 NMR titrations confirm the formation of 1 : 1 complexes between the ketones and the cations, also indicating that they should be located inside the cavity defined by the phenoxy and carbonyl oxygen atoms. Ketones 2b, 2c and 2d show transport rate sequences that follow, in general, the same trends observed in extraction and complexation for transition cations, but they are reversed for the heavy metal cations.